Jefferson scale of physician lifelong learning: translation and adaptation for the portuguese medical population. - Salgueira, Ana Paula (2009)
The competence and professionalism of doctors depend on the process of Lifelong Learning (LLL). In the Portuguese settings, in which the re-certification of physicians' skills or knowledge is currently not required, the exercise of LLL is left to personal motivation and initiative. The importance of LLL has been highlighted in numerous international recommendations and has already led, in the United States, to the development and validation of a scale for measuring physician LLL - the Jefferson Scale of Physician Life Long Learning (JSPLL). The lack of valid instruments to measure LLL adapted to the Portuguese contexts was the basis for this work, which presents the translation and adaptation of JSPLL, and the subsequent validation of the translated version to the Portuguese medical community. The translation and validation of the English version of JSPLL (JSPLL-VP) was conducted with physicians of Health Care institutions in the District of Braga, Portugal, in 2007. Methods of both qualitative (translation, assessment of the translation, retro translation) and quantitative nature (internal consistency analysis, factor analysis and analysis of response frequencies) resulted in a factor analysis that replicated, with the exception of three items, the distribution of the original scale by four factors: professional learning beliefs and motivation, scholarly activities, attention to learning opportunities and technical skills in seeking information. The results show that the JSPLL-VP is a valid Scale fit for purpose. Cronbach's alpha coefficients for the whole scale (.89) and for each factor, confirmed the internal consistency of the Scale. Additionally, differences were found between mean and standard deviations for different Scale factors. In summary, this work provides a new validated tool to monitor physician's LLL in Portugal. The transversal characterization of LLL of specific medical professionals - by specialty or by type of institution - or longitudinal studies in relation with profiles of medical training can contribute to the quality of Medical Education at the pre- or post-graduate levels.